Investigation of the Effect of Covid-19 on the New Normal Behavior of Individuals in Respect to Online Shopping - Bayat, Murat; Baydaş, Abdulvahap; Yaşar, Mehmet Emin (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This study examines the determinants of online shopping behavior during the Covid-19 pandemic, with an emphasis on the sustainability of these behavioral shifts and the product categories most significantly impacted. The research employed a convenience sampling approach, utilizing an online survey administered to 463 consumers via Google Forms. Data analysis involved the application of factor analysis, descriptive statistics (means and standard deviations), and participation level assessments to measure Covid-19 purchasing behaviors. Regression analysis and t-tests were further conducted to explore variations across demographic variables. The findings indicate that the pandemic has substantially altered consumer behavior, with approximately 39% of purchases being conducted online. The most frequently purchased items comprised protective equipment, cleaning supplies, and food products. Compared to pre-pandemic consumption patterns, respondents reported increased budgets for cleaning products, enhanced efforts to locate cost-effective options, and elevated expenditures on clothing and personal care. Conversely, spending levels for food, electronics, and small household appliances remained largely unchanged. Moreover, the analysis identified significant variations in purchasing behaviors based on age and income, whereas no significant differences were observed across gender. These results underscore the enduring impact of the pandemic on online shopping practices. This study contributes to existing literature by providing a nuanced understanding of the transformations in consumer behavior prompted by the Covid-19 pandemic, offering critical insights for businesses and policymakers adapting to the evolving digital marketplace.